Performance improvement in distribution network with DG - Siti Rafidah, Abdul Rahim; Titik Khawa, Abdul Rahman, Dr.; Ismail, Musirin, Dr.; Syahrul Ashikin, Azmi; Mohd Fayzul, Mohammned; Muhd Hatta, Hussain; Mohammad Faridun Naim, Tajuddin (Universiti Teknologi MARA (UiTM), 2011)
Organized by Universiti Teknology MARA, 4th - 5th June 2008 at Grand Blue Wave Hotel, Shah Alam, Selangor, Malaysia.